1963
DOI: 10.1063/1.1733801
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Isotope Effect in Photochlorination of H2, CH4, CHCl3, and C2H6

Abstract: The relative rates of hydrogen and deuterium abstraction by chlorine atoms from H2–D2, CH4–CD4, and C2H6–C2D6 in direct competition have been studied by a mass spectrometer technique permitting direct determinations of rates. The pair CHCl3–CDCl3 was investigated by a substitution—addition competition with C2Cl4. Data were obtained between 300° and 475°K, and values of kH/kD ranged between 3.64 and 10.9 for CH4/CD4, 2.37 to 2.69 for C2H6/C2D6, 1.58 to 2.26 for CHCl3/CDCl3, and 4.7 to 8.9 for H2/D2. For the fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1

Year Published

1970
1970
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 18 publications
7
57
1
Order By: Relevance
“…Our data on the C2H6/C2D6 system are in close agreement with those of Chiltz et al (10). The isotope effect is rather weak compared to the so-called "theoretical maximum", which is based on a one-dimensional three-particle model but which ignores any tunneling correction.…”
Section: Isotope Effectssupporting
confidence: 91%
See 1 more Smart Citation
“…Our data on the C2H6/C2D6 system are in close agreement with those of Chiltz et al (10). The isotope effect is rather weak compared to the so-called "theoretical maximum", which is based on a one-dimensional three-particle model but which ignores any tunneling correction.…”
Section: Isotope Effectssupporting
confidence: 91%
“…Chiltz et al (10) reported the rate constant ratios, kl/k2, at several temperatures in the range 302-433 K for the direct competition in C2H6/C2D6 mixtures using a mass spectrometric technique. Although these data show a high degree of scatter when plotted according to the Arrhenius rate law, an approximate temperature dependence is given by In (kl/kl) = 0.53 + 137/T, in satisfactory agreement with our value of In (k,/kz) = 0.545 + 151/T based on the data in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, both the magnitude and the trend in activation energy with the heat of reaction for chlorine atom attack in chloromethanes and chloroethanes is predicted, contrary to experiments (6). Furthermore, the chlorination of C2H6/C2D6 is one of the few examples of the failure of the BEBO method for the calculation of kie (3,7). In the case of ethyl chloride the situation might have been expected to be even worse based on the arguments of Johnston and Goldfinger (6) that the preferential attraction of the chlorine atom by the bound chlorine may result in collision complexes of the form C-Cl---Cl superseding those of the form C-H---Cl to the extent that in the case of a molecule such as CHCl, a hydrogen atom transfer complex may never be formed.…”
Section: Bebo Calculationsmentioning
confidence: 88%
“…In the case of several classes of reactions to which abstractions by chlorine atoms belong, the BEBO method is known to fail (3,5). Generally, activation energies can be calculated to within 1 or 2 kcal/mol compared with the experimental data, whereas abstractions of hydrogen by chlorine atoms are predicted to have activation energies much higher than those observed, frequently by [6][7] For personal use only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation